2010
DOI: 10.1007/s11746-010-1608-8
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Growing Region, Cultivar and Harvest Timing on the Diversity of Australian Olive Oil

Abstract: The quality indices and chemical composition of ten common olive cultivars grown in different regions of Australia were evaluated to determine the diversity of olive oils produced in Australia. Olives from trees from different environments including warmer climates in the north to colder climates in the south were sampled at two different stages of maturity over 2 years. The oil was extracted and standard methods were used to analyse the oil. Oleic acid content ranged from 83.4% in the Picual cultivar grown in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
99
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 16 publications
(14 reference statements)
19
99
2
2
Order By: Relevance
“…Other authors (Samaniego-Sánchez, Quesada-Granados, López-García de la Serrana, & López-Martínez, 2010) have reported a total wax ester content in Picual variety of between 62.80 and 76.29 mg/kg, as obtained by a cold extraction system, which is below the generally reported values for extra-virgin olive oil. Pérez-Camino et al (2003) reported wax values ( P C40ÀC46) for extra virgin olive oils as low as 27 mg/kg, similar to that reported by Mailer, Ayton, and Graham (2010) for olive oils from Coratina variety grown in Australia.…”
Section: Resultssupporting
confidence: 75%
“…Other authors (Samaniego-Sánchez, Quesada-Granados, López-García de la Serrana, & López-Martínez, 2010) have reported a total wax ester content in Picual variety of between 62.80 and 76.29 mg/kg, as obtained by a cold extraction system, which is below the generally reported values for extra-virgin olive oil. Pérez-Camino et al (2003) reported wax values ( P C40ÀC46) for extra virgin olive oils as low as 27 mg/kg, similar to that reported by Mailer, Ayton, and Graham (2010) for olive oils from Coratina variety grown in Australia.…”
Section: Resultssupporting
confidence: 75%
“…It has been shown than geographic and climatic conditions of production areas may affect the quality and composition of olive oils (Mailer, Ayton, & Graham, 2010). Therefore, relationships of TPC and antioxidant properties with altitude, maximum and minimum temperature and rainfalls of the different region were analysed in the current assay.…”
Section: Chemical Extractsmentioning
confidence: 99%
“…The olive ripening stage plays a crucial role in chemical and sensory qualities of the oils (Aparicio & Morales, 1998;Mailer, Ayton, & Graham, 2010). With the purpose of reducing the effect of the degree of maturation on oil characteristics, all productions were transformed to a similar ripening index (RI) corresponding to about 50% pigmentation of the olive skin.…”
Section: Olive Sampling and Processingmentioning
confidence: 99%